Empirical analysis of investors' reaction to individual vs group-written research reports - Chow, Cheong Yean (Nanyang Technological University, 2008)
The objective of this research is to investigate whether investors perceive that research reports written by a team of analysts is of higher quality than those written by an individual analyst. The statistical tests show that investors react more strongly to team-analyst reports than individual-analyst reports. Specifically, the abnormal returns on publication of individual-analyst reports are significantly lower than those for team-analyst reports, thus supporting our hypothesis and the behavioural decision-making theory.